2016
DOI: 10.1093/mnras/stw1024
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the UV spectrum of SDSS-III/BOSS galaxies: hints towards the detection of the UV upturn at high-z

Abstract: We exploit stellar population models of absorption line indices in the ultraviolet (from 2000 -3200Å) to study the spectra of massive galaxies. Our central aim is to investigate the occurrence at high-redshift of the UV upturn, i.e. the increased UV emission due to old stars observed in massive galaxies and spiral bulges in the local Universe. We use a large (∼ 275, 000) sample of z ∼ 0.6 massive (M * /M > 11.5) galaxies using both individual spectra and stacks and employ a suite of models including a UV con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 59 publications
9
31
0
Order By: Relevance
“…In the first panel we also show the underlying C09 model showing the contribution of the purely old population, clearly demonstrating that the extra blackbody component only contributes to the UV part of the SED. The fitted blackbody component usually has a temperature between 10,000 and ∼ 21, 000K, consistent with the earlier UIT observations of Brown et al (1997) and the indices derived by Le Cras et al (2016) for massive BOSS galaxies. We plot the derived temperature vs. M r (a good proxy for stellar mass) in Fig.…”
Section: Blackbody Fittingsupporting
confidence: 88%
“…In the first panel we also show the underlying C09 model showing the contribution of the purely old population, clearly demonstrating that the extra blackbody component only contributes to the UV part of the SED. The fitted blackbody component usually has a temperature between 10,000 and ∼ 21, 000K, consistent with the earlier UIT observations of Brown et al (1997) and the indices derived by Le Cras et al (2016) for massive BOSS galaxies. We plot the derived temperature vs. M r (a good proxy for stellar mass) in Fig.…”
Section: Blackbody Fittingsupporting
confidence: 88%
“…In this case, a pure old SSP is a good first approximation for a galaxy whose mass is larger than 10 && M ⨀ , such as the stacked spectra analysed here. However, as shown in Figure 1 and Extended Data Figure 4, the NUV data clearly indicates the inability of an old SSP to fully describe the SFH of massive ETGs, and calls for an additional component 3,14 to be fitted. This component needs to be a very hot stellar population responsible for the decrease of NUV absorption features possibly due to young stars.…”
Section: Methodsmentioning
confidence: 99%
“…We used the version of E-MILES that extends down to 6.3 Myr 40 and employ the Padova isochrones 41 . The grid of models spans metallicities, -2.32 ≤ [M/H] ≤ +0.22, with ages ranging from 6.3 Myr to 14 Gyr. We adopt a low-mass tapered bimodal initial mass function with logarithmic slope of 1.3, and scaled-solar abundances 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data to z = 0.55 are broadly consistent with previous work by Brown et al (1998bBrown et al ( , 2000aBrown et al ( , 2003 on the brightest galaxies in clusters in the sense that both sets of studies detect upturns in cluster populations out to this redshift. Le Cras et al (2016) use a series of indices (developed by Fanelli et al 1992) to measure the strength of the hot HB population in BOSS Luminous Red Galaxies and show evidence for a decline in the upturn strength at z > 0.6, though with a subset of the most massive galaxies showing an upturn even at z = 1. A caveat on this is that some of the indices used in their work also have some sensitivity to star formation, and Roseboom et al (2006) has shown that there is a large fraction of post-starburst galaxies in the LRG sample.…”
Section: Helium Rich Stars As the Source Of The Uv Upturnmentioning
confidence: 99%